O PROBLEMIE POROZBIOROWYCH DZIEJÓW III STATUTU LITEWSKIEGO W POLSKIEJ LITERATURZE HISTORYCZNOPRAWNEJ - Godek, Sławomir (Zeszyty Prawnicze, 2017)
Post-Partition History of the Third Statute of Lithuania Problem in the Polish Historical-Legal Literature Summary The third Statute of Lithuania from 1588 constituted a prolonged codification. Following the fall of Commonwealth (of Poland and Lithuania), it was binding until 1840 within the Lithuanian-Russian territory, which made up a part of the Russian Empire as a result of the partitions. In the rich Polish historical-legal literature devoted to the Statute, there are neither case studies on the gradual decadence of that codification, nor on its exchange by the Russian law. This results to some extent from a limited research on the Lithuanian history, conducted in the second half of the 19th century and first half of the 20th century, which constitutes a significant shortcoming. It is peculiar that we know nothing about the last decades during which the codification was in force; whereas, commencing 1588, the codification distinctively influenced legal relations within the enormous territories of the Commonwealth, as well as in the neighboring countries. The lack of knowledge on the circumstances of the third Statute being annulled, also prevents full recognition of the Russification process on the Lithuanian territory.